Does the Dispersion of Unit Labor Cost Dynamics in the EMU Imply Long-run Divergence? Results from a Comparison with the United States of America and Germany - Sebastian Dullien; Ulrich Fritsche (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Using unit labor cost (ULC) data from Euro area countries as well as US States and German Lander we investigate inflation convergence using different approaches, namely panel unit root tests, cointegration tests and error-correction models. All in all we cannot reject convergence of ULC growth in EMU, however, country-specific deviations from the rest of the currency union are much more pronounced and much more persistent in Europe. This holds before and after the introduction of the common currency. Due to its implications for the real exchange rate in levels this gives rise to serious concern.
Keywords: C32; O47; E31; 330; Unit labor costs; inflation; EMU; convergence; panel unit root tests; convergence clubs; Inflationsrate; Inflationskonvergenz; Europäische Wirtschafts- und Währungsunion; Lohnstückkosten; Vergleich; EU-Staaten; USA; Deutschland